2021
DOI: 10.3390/ijms222312939
|View full text |Cite
|
Sign up to set email alerts
|

Lignin and Xylan as Interface Engineering Additives for Improved Environmental Durability of Sustainable Cellulose Nanopapers

Abstract: Cellulose materials and products are frequently affected by environmental factors such as light, temperature, and humidity. Simulated UV irradiation, heat, and moisture exposure were comprehensively used to characterize changes in cellulose nanopaper (NP) tensile properties. For the preparation of NP, high-purity cellulose from old, unused filter paper waste was used. Lignin and xylan were used as sustainable green interface engineering modifiers for NP due to their structural compatibility, low price, nontoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…In this comparison, the most characteristic peak of cellulose was -OH group absorbance around 3300 cm −1 . The distinct peaks of wax were visible at 2915 and 2849 cm −1 , representing the stretching of CH 2 groups [ 28 , 35 ], which matches well with cellulose CH and CH 2 signals [ 27 ], but in terms of visual appearance are significantly different with the pronounced shape of the two peaks. Unique to wax is the signal at 1731 cm −1 , which corresponds to the carbonyl group of the fatty acid ester linkage [ 28 , 35 ].…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…In this comparison, the most characteristic peak of cellulose was -OH group absorbance around 3300 cm −1 . The distinct peaks of wax were visible at 2915 and 2849 cm −1 , representing the stretching of CH 2 groups [ 28 , 35 ], which matches well with cellulose CH and CH 2 signals [ 27 ], but in terms of visual appearance are significantly different with the pronounced shape of the two peaks. Unique to wax is the signal at 1731 cm −1 , which corresponds to the carbonyl group of the fatty acid ester linkage [ 28 , 35 ].…”
Section: Resultsmentioning
confidence: 80%
“…CNP and MNP samples were dip-coated to compare the nanopaper’s microstructure’s impact on the resulting contact angle values ( Figure 6 c). As demonstrated in our previous research, the pure CNP is more porous and has more hydroxyl groups on the surface compared to MNP [ 27 ]. The initial θ values showed that MNP and CNP are both highly hydrophilic, but MNP has an initial value of 31°, which is 3 times higher compared to CNP.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Nanocellulose, defined as less than 100 nm in diameter, has attracted growing interest for many applications because of its functional properties such as nano size, high surface area, amphiphilic property, low density, high mechanical strength, eco-friendliness, nontoxicity, and low cost [3,4]. Nanocellulose functions as a composite film [5], performs the encapsulation and delivery of vitamin D 3 [6], serves as a reinforcement material [1], an emulsifier [7], and can be used in energy applications [8], active packaging [8], cosmetics [9], and cellulose nanopapers [10]. Nanocellulose has been classified as three types, including (1) cellulose nanocrystal (CNC)/nanocrystalline cellulose (NCC) which is a rod-like crystalline region cellulose; (2) cellulose nanofibril (CNF)/nanofibrillated cellulose (NFC) which is a long entangled cellulose with amorphous and crystalline regions; and (3) bacterial cellulose (BC) produced from bacteria [11].…”
Section: Introductionmentioning
confidence: 99%